International and National Laws Relations: Interrelated and Interacting Law Source - Katjong, Kadir (Papua Law Journal, 2017)
The existences of international and national laws are interrelated and interacting. The linkage of International and National laws is depicted in monism and dualism theories. The existence of international and national laws is examined by looking at each others interdependence and interaction between the two. The object of this paper is related to the disengagement and interaction between international law and national law, using normative juridical methods. The results show that in actual practice between international and national laws need and influence each other, includes: international law is more effective if transformed into the national law; international law will bridge when the national law cannot be applied in the territory of other countries; international law will harmonize the differences in the national law; and international law more grow from the practices of countries. Extradition as one example, in principle contains two dimensions of interrelated international and national.